A UK survey of current ENT practice in the assessment of nasal patency. Issue 8 (27th June 2017) - Andrews, P; Joseph, J; Li, C-H; Nip, L; Jacques, T; Leung, T
Abstract: Background: Nasal obstruction is a common ENT complaint; however, decisions on its management are challenging, with high rates of dissatisfaction following surgery. This study investigated the practice of UK clinicians in the evaluation of nasal patency. Method: Seventy-eight UK-based rhinologists were surveyed at the 2015 British Academic Conference in Otolaryngology. Results: Clinical history and examination are almost universally used to evaluate nasal blockage. The most commonly used test was the nasal misting pattern (73 per cent), followed by peak nasal inspiratory flow (19 per cent). The Sino-Nasal Outcome Test 22 or 23 was utilised by 29 per cent of respondents. Sixty-three per cent of respondents reported that a lack of equipment was the principle reason for not using objective measures, followed by time constraints and a lack of correlation with symptom scores. Conclusion: British clinicians rely on clinical skills to evaluate nasal blockage. There is a desire for a simple, non-invasive device that objectively measures airflow for nasal breathing during physiological resting and correlates with subjective symptom scores.